PENERAPAN KURIKULUM MERDEKA PADA MATA PELAJARAN FIQIH KELAS IV ADI MIN 9 BIREUEN - Edi Saputra (LPPM IAI Almuslim Aceh, 2023)
The problem of this research is what is the general description of MIN 9 Bireuen, what is the theoretical basis of the independent curriculum and what are the principles of independent doctrine in class IV A fiqh subjects. This research aims to find out the general description of MIN 9 Bireuen, to find out the theoretical basis of the independent curriculum, and To find out the application of the independent curriculum in class IV A Fiqh subjects. This type of research is field research using a qualitative approach. In the data collection process, the author used observation, interview and documentation techniques. In analyzing the data the author carried out three stages, namely reduction, display and verification. Research results: First, MIN 9 Bireuen is located on Jalan Pulo Siron Number 3, Dayah Mesjid Village, Kutablang District. Second, freedom to learn is the policy of the Ministry of Education and Culture of the Republic of Indonesia. The Independent Curriculum is implemented with the aim of training students' independence in thinking. Independent learning prioritizes students' interests and talents which can foster creative and fun attitudes in students. Third, independent curriculum planning is carried out by sending teachers to take part in technical guidance training both online and in person, then preparing learning tools so that learning can run optimally. One way of implementing an independent curriculum in learning is using differentiated learning and assessment.